The effects of kangaroo care on delirium management in neonates under non-invasive mechanical ventilation: A randomized control trial - Kayvan Mirnia; Jason W. Osborne; Hamid Sharif-Nia; David Sánchez-Teruel; Fatemeh Khoshnavay Fomani; Nasim Mirzaei (Nursing Practice Today)
Background & Aims: Little is known about managing delirium in neonates admitted to Neonatal Intensive Care Units. The current study investigated whether kangaroo mother care can affect neonates' delirium under non-invasive mechanical ventilation. Materials & Methods: In this randomized control trial, a total of 50 term neonates who were under non-invasive mechanical ventilation were allocated to intervention and control groups (n=25 in each group) using block randomization. Utilizing “Cornell Assessment of Pediatric Delirium”, and “ACoRN respiratory sequence protocol”, the data were gathered at baseline, 24, 48, and 72 hours after. The intervention group received 30 minutes of kangaroo mother care daily. Results: There was a statistical delirium mean scores difference between the two groups on day 2 (p < 0.045) but not on other days. Repeated measures modeling (linear mixed models and generalized linear mixed models) indicated significant differences in change curves for both Cornell Assessment of Pediatric Delirium scores and the incidence of delirium. Conclusion: Implementing kangaroo mother care for a 30-minute duration each day for neonates under non-invasive mechanical ventilation may markedly decrease delirium occurrence.